2023
DOI: 10.1186/s40634-023-00665-1
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells for the treatment of early to moderate osteoarthritis of the knee: a systematic review

Theofylaktos Kyriakidis,
Charalampos Pitsilos,
Myrto Iosifidou
et al.

Abstract: Purpose Mesenchymal stem cells (MSCs) present a valuable treatment option for knee osteoarthritis with promising results. The purpose of the present study was to systematically review the clinical and functional outcomes following mesenchymal stem cell application focusing on early to moderate knee osteoarthritis. Methods A systematic search was done using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines in Pubmed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
(119 reference statements)
0
1
0
Order By: Relevance
“…They concluded that MSC injection is effective for treating knee OA, and the curative effect should be maintained for no less than 12 months, during which the WOMAC pain score, VAS score, WOMAC stiffness score, and WOMAC physical function improve 27 . In another review, 12 articles comprising 539 patients and 576 knees treated with a single intraarticular injection of MSCs for knee OA were analyzed by Kyriakidis et al (2023) 28 , who reported that MSC injection is a safe and effective treatment for K-L grade I-III knee OA. Interestingly, a triple-blinded, placebo-controlled, randomized trial compared the treatment efficacy of allogeneic MSCs (from adipose tissue) to that of normal saline (control group) and confirmed that allogeneic MSC injection is safe and significantly improves treatment efficacy 29 .…”
Section: Expanded Mesenchymal Stem Cellsmentioning
confidence: 99%
“…They concluded that MSC injection is effective for treating knee OA, and the curative effect should be maintained for no less than 12 months, during which the WOMAC pain score, VAS score, WOMAC stiffness score, and WOMAC physical function improve 27 . In another review, 12 articles comprising 539 patients and 576 knees treated with a single intraarticular injection of MSCs for knee OA were analyzed by Kyriakidis et al (2023) 28 , who reported that MSC injection is a safe and effective treatment for K-L grade I-III knee OA. Interestingly, a triple-blinded, placebo-controlled, randomized trial compared the treatment efficacy of allogeneic MSCs (from adipose tissue) to that of normal saline (control group) and confirmed that allogeneic MSC injection is safe and significantly improves treatment efficacy 29 .…”
Section: Expanded Mesenchymal Stem Cellsmentioning
confidence: 99%
“…In the early stages of valgus osteoarthritis, conservative treatment is the preferred treatment and includes exercise, weight loss, pharmacological treatments (NSAIDs) and unloader braces [ 8 ]. In addition, there appears to be a growing interest in alternative therapies, including acupuncture, PRP injections, stem cell injections and dry needling [ 9 , 10 , 11 , 12 ]. A recent systematic review and meta-analysis showed very low-quality evidence for a possible positive short-term effect on osteoarthritis concerning pain intensity and improving physical function [ 13 ].…”
Section: Introductionmentioning
confidence: 99%